2019
DOI: 10.1097/bsd.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cervical Spinal Muscle Degeneration on Cervical Sagittal Balance and Spinal Degenerative Disorders

Abstract: Study Design: This is a retrospective analysis of kinematic magnetic resonance images (kMRI). Objective: To assess the association of cervical paraspinal muscle with cervical sagittal balance and degenerative spinal disorders. Summary of Background Data: Although the effects of spinal disorders and cervical imbalance on patient’s symptoms have been well described, the relationship of the cervical muscle qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
42
1
Order By: Relevance
“…Older age and higher BMI were associated with FI of the PVM, helping to validate the novel method used to measure FI in this investigation, given that such associations have been corroborated by past research [12,18]. Investigators have employed both MRI-and CT-based techniques to assess the quality of the PVM [13,18,20]. MRI-based modalities have quantified FI as a percentage of the PVM volume by using differences in the T2-weighted signals of fat and muscle tissue [13].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Older age and higher BMI were associated with FI of the PVM, helping to validate the novel method used to measure FI in this investigation, given that such associations have been corroborated by past research [12,18]. Investigators have employed both MRI-and CT-based techniques to assess the quality of the PVM [13,18,20]. MRI-based modalities have quantified FI as a percentage of the PVM volume by using differences in the T2-weighted signals of fat and muscle tissue [13].…”
Section: Discussionsupporting
confidence: 57%
“…Investigators have employed both MRI-and CT-based techniques to assess the quality of the PVM [13,18,20]. MRI-based modalities have quantified FI as a percentage of the PVM volume by using differences in the T2-weighted signals of fat and muscle tissue [13]. On the other hand, CT-based studies have reported the "mean density" of the PVM (averaged density over a fixed contour) expressed in Hounsfield units (HU) [18], with a lower density corresponding to a fattier PVM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, thoracic inlet parameters were found to exhibit a strong correlation with the other cervical parameters [14][15][16] . Therefore, assessing the impact of these parameters on ANP in the context of CK is a key imperative.…”
Section: Discussionmentioning
confidence: 87%
“…Previous researchers proved thoracic inlet parameters correlates highly with the other cervical parameters and had a critical effect on cervical sagittal alignment [14][15][16] . Therefore, it is necessary to discuss the impact of thoracic inlet parameters on ANP in CK.…”
Section: Discussionmentioning
confidence: 99%